(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article deals with the issues of the ecology of the city of Bishkek, the study of the ecological features of the soil cover, as the basis of the ecological environment, in particular, the contamination of the soil cover, the study of the chemical composition of soils, contamination with radionuclides.